2018
DOI: 10.1111/cobi.13033
|View full text |Cite
|
Sign up to set email alerts
|

Biofluorescence as a survey tool for cryptic marine species

Abstract: As ecosystems come under increasing anthropogenic pressure, rare species face the highest risk of extinction. Paradoxically, data necessary to evaluate the conservation status of rare species are often lacking because of the challenges of detecting species with low abundance. One group of fishes subject to this undersampling bias are those with cryptic body patterns. Twenty-one percent of cryptic fish species assessed for their extinction risk (International Union for Conservation of Nature [IUCN]) are data de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Increasing underwater technology that will facilitate detection (e.g. via fluorescence) and photographic capture of CRFs is likely to further increase their contribution to the diving industry (De Brauwer et al , ).…”
Section: Ecology and Functional Role Of Crfsmentioning
confidence: 99%
“…Increasing underwater technology that will facilitate detection (e.g. via fluorescence) and photographic capture of CRFs is likely to further increase their contribution to the diving industry (De Brauwer et al , ).…”
Section: Ecology and Functional Role Of Crfsmentioning
confidence: 99%
“…Fluorescence may occur in fishes belonging to different species, in part still unidentified because of a cryptic living behavior. In fishes populating coral reef areas biofluorescence has been recommended as a valuable tool in the search and surveillance of otherwise poorly detectable rare species [203]. It has been also reported that many of the fluorescing fishes, including sharks and rays, possess a good vision and the presence of intraocular yellow filters, likely facilitating their ability to detect this fluorescence at wavelengths longer than the blue or dark in aquatic environment.…”
Section: Fishesmentioning
confidence: 99%
“…bargibant and H . denise ) and also pipefish species of the Syngnathidae family, in relation to the occurrence of green and red biofluorescence [13,14,7,3].…”
Section: Discussionmentioning
confidence: 99%
“…bargibant and H . denise [13], especially in relation to the eyes. Green fluorescence has been reported to attract preys in hydromedusa and has an effective result during day light [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation